Hazing: destroying young lives - Nuwer, Hank (Indiana University Press, 2018)
Introduction : the perils of hazing / Hank Nuwer -- Dead to rites : the chlorine poisoning of Henrietta Jackson / Hank Nuwer -- Hazing in fraternities and sororities : a primer / Hank Nuwer -- A need for transparency : parents, students must make informed decisions about Greek-life risks / Douglas Fierberg and Chloe Neely -- Shame : the hidden harm of hazing for victims and hazers / Tracy Maxwell -- Sexual hazing : a wrongful passage / Norm Pollard -- Ill met by moonlight : the first fraternity hazing death / Hank Nuwer -- Eliminating band hazing : what must be done / Malinda Matney -- Hazing and gender : lenses for prevention / Elizabeth J. Allan and Morgan B. Kinney -- Listening to the voices of the hazed : an examination of race, violence, and black fraternity membership / Ashley Stone -- Unspoken sisterhood : women in African-American sororities and their physical and mental ordeals-"weeding the good from the bad" / Gina Lee-Olukoya -- Sexually exploitive athletic hazing and Title IX in the public school locker room : warriors, machismo, and jockstraps / Susan P. Stuart -- A mother's story : I lost my child to fraternity hazing / Debbie Smith with Stacey Kennelly -- How alfred university ended the greek system to become a hazing research institution / Norm Pollard -- How schools may have facilitated and operationalized hazing : an interview with Peter F. Lake, author of The rights and responsibilities of the modern university / Hank Nuwer -- A fraternity model : addressing campus alcohol misuse and abuse / Edward G Whipple and Robert A. Biggs -- A realistic approach to public relations for fraternities in crisis / Ray Begovich -- A sorority hazing hero incurs the wrath of alums / Sarah Wild -- How reforms and reformers played a role in changing a hazing culture / Allison Swick-Duttine -- Hazing hides in plain sight : an open letter to hazers from a nationally known speaker / David Westol -- Hazing and university ethics : the need for faculty involvement and guidance / James F. Keenan, SJ -- Understanding hazing in the perilous world of guyland : an interview with Michael Kimmel / Hank Nuwer -- An unsolved cold case : how did Joe Bisanz die? / Hank Nuwer -- Women and a feminine leadership style can defeat hazing / Tracy Maxwell -- The Purdue tank scrap / David Hovde -- A blueprint for Greek reforms : how to establish an antihazing task force with concrete "good first steps" to change a hazing culture / Travis T. Apgar -- Hazing and the law and litigation : what you need to know / R. Brian Crow and Colleen McGlone -- Smokeouts and smokescreens : military hazing / Hank Nuwer